2012
DOI: 10.1002/ijc.27796
|View full text |Cite
|
Sign up to set email alerts
|

Androgen deprivation results in time‐dependent hypoxia in LNCaP prostate tumours: Informed scheduling of the bioreductive drug AQ4N improves treatment response

Abstract: Androgen withdrawal induces hypoxia in androgen-sensitive tissue; this is important as in the tumour microenvironment, hypoxia is known to drive malignant progression. Our study examined the time-dependent effect of androgen deprivation therapy (ADT) on tumour oxygenation and investigated the role of ADT-induced hypoxia on malignant progression in prostate tumours. LNCaP xenografted tumours were treated with anti-androgens and tumour oxygenation measured. Dorsal skin fold (DSF) chambers were used to image tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 33 publications
10
65
0
Order By: Relevance
“…55 Studies in our laboratory showed that mice bearing LNCaP xenografts exposed to bicalutamide-induced hypoxia had increased metastasis to the lungs; this correlated with an increase in Bcl2 and reduction in Bax. 44 Gene amplification has also been reported in rodent tumour cells exposed ex vivo or in vivo to hypoxia; this was associated with an increase in metastases. 65,66 In both tissue culture and animal models, acute hypoxia/reoxygenation have been linked to the induction of DNA strand breaks and clearly, if these breaks are not repaired, they will result in further mutations.…”
Section: Variability In Tumour Oxygenationmentioning
confidence: 94%
See 4 more Smart Citations
“…55 Studies in our laboratory showed that mice bearing LNCaP xenografts exposed to bicalutamide-induced hypoxia had increased metastasis to the lungs; this correlated with an increase in Bcl2 and reduction in Bax. 44 Gene amplification has also been reported in rodent tumour cells exposed ex vivo or in vivo to hypoxia; this was associated with an increase in metastases. 65,66 In both tissue culture and animal models, acute hypoxia/reoxygenation have been linked to the induction of DNA strand breaks and clearly, if these breaks are not repaired, they will result in further mutations.…”
Section: Variability In Tumour Oxygenationmentioning
confidence: 94%
“…43 More recently, we have shown that the median oxygen level of bicalutamide-treated LNCaP prostate xenografts remained below 0.1% oxygen for more than 10 days. 44 Overall, survival in this extreme stress will drive selection for malignant phenotypes that are governed by a Darwinian selection process. 45 …”
Section: Pathological Hypoxiamentioning
confidence: 99%
See 3 more Smart Citations